Perlakuan Akuntansi Aset Tetap Berbasis Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (SAK – ETAP) - Sivanissa, Nabilla; Setiawan, Wawan Lulus; Susantira, Innas (Jurnal Riset Manajemen Indonesia, 2023)
This research aims to determine the extent of implementation of SAK-ETAP in the Mulia Consumer Cooperative. The research method used is a quantitative descriptive method. The data analysis technique used is descriptive and uses primary and secondary data. The results of this research found that the Mulia Consumer Cooperative has not fully implemented SAK-ETAP in the accounting treatment of fixed assets. Most accounting treatments are in accordance with SAK-ETAP, however, there are several accounting treatments for fixed assets that are not appropriate, namely inventory, equipment, and vehicles, which are not separated in their recording and presentation. Cooperatives do not calculate the depreciation value of vehicles, which should be calculated and recorded every year.